Life from bad smells - Stiller-Reeve, Mathew; Rosnes, Erling; Eilertsen, Mari; Ramalho, Sofia; Poddevin, Victor; Panieri, Giuliana; Peftieva, Olena (Septentrio Educational, 2023)
Focus: To understand that hydrogen sulphide indicates that there is life at the bottom of the deep-sea. Learning objectives: With this activity, we create a nasty smell similar to hydrogen sulphide from rotting organic matter. We use that smell as a foundation for a discussion/lesson on interesting life, animals and food webs from the deep sea floor. Key words: Deep-sea, hydrogen sulphide, chemosynthesis, nematodes, tube worms, food webs.